Phosphorus cycling during decomposition of plant residues in weathered soils from the tropics: influence of plant factors - Salas, Ana M., author; Elliott, Edward T., advisor; Westfall, Dwayne G., advisor (Colorado State University. Libraries, 2001)
Increasing interest in incorporation of plant residues into soils in tropical cropping systems has focused attention on the identification of plant quality factors controlling P cycling. In this study the primary objective was to evaluate the influence of selected plant characteristics on P availability during decomposition. Residues of sorghum (Sorghum bicolor) and crotalaria (Crotalaria juncea) having the same C:P ratio but differing in the content of water extractable Pi, enzymatic activities and quality of C compounds were compared for their ability to enhance the resin P and Bray extractable P levels in two acid soils (an Alfisol and an Ultisol) from the tropics. In order to elucidate the mechanisms involved, soil phosphatase activities, pattern of P release from the residues, as well as microbial P dynamics were investigated during laboratory incubations. The role of changes in microbial community composition and immobilization of P in decomposing residues were also evaluated for their contribution to explain differences in turnover of microbial P and P availability. Covariance analysis revealed that crotalaria residue had on average, 75 and 40 % higher Bray P for low (330) and high C:P (630) ratio, respectively, as compared with sorghum residue. To investigate this substrate dependency several mechanisms were tested. Results indicated a relationship between plant phosphatase activity and soil phosphatase activity only for the Ultisol. Pattern of release of P from the residues showed that both residues released more than 90% of the total P in the first 5 days of decomposition; no differences existed between residues types. Plant enzymatic activity and release of P from residues could not satisfactorily account for differences in P availability from the different residues. Dynamics of microbial biomass P significantly differed between residues. Sorghum residue showed significantly higher values of microbial P and the rate of microbial P loss was lower as compared with crotalaria. This suggests that P immobilization and turnover of microbial P was affected differently by the residue type. Different patterns of P immobilization in decomposing residues supported this conclusion. P immobilization in the sorghum residue was 2-4 times higher than in crotalaria, and represented up to 30% of the total plant P added. This immobilization of P in the decomposing residues could account for observed differences in P availability between the residues. Residue types also affected soil fungal biomass. A correspondence between colonization of the Particulate Organic Matter (POM) by soil fungi and P accumulation in the decomposing residues confirmed that changes in soil microbial community structure can affect the pattern of P immobilization. Phosphorus cycling was thus influenced by changes in turnover of decomposer communities driven by residue types. Although the mechanisms shaping microbial communities were not completely understood, results point out the significance of plant factors, other than C:P ratio, in determining short-term P availability from plant residues.
Keywords: soil sciences